Thoracoscopic T2-T3 versus T4 sympathectomy for primary palmar hyperhidrosis in children and adolescents: a randomized comparative study - Ismael Essam Elhalaby; Mohamed Awad Mansour; Ahmed Mohamed Ismail Tawfik; Hisham Fayad Aly (SpringerOpen, 2021)
Abstract Background Controversy exists regarding the appropriate level of sympathectomy for primary palmar hyperhidrosis (PH) as different levels are associated with variable postoperative patients' satisfaction and potential complications. The aim of this study was to investigate the safety, efficacy, and outcome of T2-T3 thoracoscopic sympathectomy (TS) versus T4 TS in this age group. Results This prospective study included 32 patients (17 males and 15 females) with primary PH treated at the department of pediatric surgery, in our institution during the period from February 2019 to February 2020. Inclusion criteria included moderate and/or severe degrees of PH not responding to conservative measures. The patients were divided randomly into two groups: group I treated by T2-T3 TS and group II underwent only T4 TS. All patients were evaluated regarding operative details and postoperative outcome. Follow-up ranged from 6 to 24 months. Group I included 18 patients (14 operated on both sides and 4 operated on one side), and group II included 14 patients (11 operated on both sides and 3 operated on one side). The ages ranged between 5 and 18 years (mean 14.25 ± 3.14 years). The difference in mean age among both groups (14.5 versus 13.9 years) was not statistically significant. The mean operative time was significantly longer in group I (22.4 versus 17.2 min, p value 0.046). The hospital stay (1 day) was similar for both groups. Postoperative compensatory hyperhidrosis (CH) was more frequent in group I (n=7, 50% versus n=5, 45.5%), but the difference was not statistically significant. Postoperative over dryness occurred in 5 patients in group I (28.6%) and temporary Horner's syndrome in one patient (7.14%). No over dryness or Horner's syndrome occurred in any patient in group II. The QOL score has improved in both groups; the degree of improvements was better in group II. Conclusion Both T2-T3 TS and T4 TS are effective in treating primary palmar hyperhidrosis in children and adolescents. T4 TS is preferred than T2-3 TS due to less frequent postoperative complications and better patients' satisfaction.